Hydraulic flow model of plant organs in response to physical and environmental factors. (October 2017) - Lahkar, Bhrigu Kumar; Bera, Tarun Kumar
A mechanistic hydraulic flow model based upon plant physiological behavior is proposed in this work to determine functionality of different plant organs in handling flows of water. The model is developed by introducing various standard elements in bond graph lexicon. Out of all the resistive elements of plants, stem xylem resistance and stomatal resistance are modeled by taking diurnal variation. The value of stem xylem resistance of the plant is the maximum value at midday (2 . 96 × 10 7 MPa s/m 3 ) and the minimum value (2 . 4 × 10 7 MPa s/m 3 ) in the dark period. A Jarvis–Stewart type model for stomatal conductance is implemented for developing stomatal resistance. The process of transpiration which is formulated with the help of Ohm's law analogy is also incorporated in the model. Thermal behavior of the vegetation is introduced by taking the boundary layer, aerodynamics, ambient temperature, relative humidity and global solar radiation into account. Simulations are performed for specific kinds of plants and for specific sights. Finally, various environmental and physical influencing factors are considered to study the response of the plant model, and this modeling technique offers a novel modeling tactic alternative to field measurements. The transpirational flow at constant water potential of −0.15 MPa varies between1 . 2 × 10 − 8 to2 . 25 × 10 − 8 m 3 /s during the day period. The rate of transpiration reaches a maximum value of about2 . 0 × 10 − 8 m 3 /s during the early hours in each day while the value of solar radiation is about 700 Wm −2 . Leaf water potential depletes to a minimum value of −1.5 MPa at the 5 th day of the drying cycle period.